Respuesta :
Answer:
Stephen's claim is correct.
Step-by-step explanation:
The given function is
[tex]f(x)=(x+3)(x+5)[/tex]
Put x=0 to find the y-intercepts.
[tex]f(0)=(0+3)(0+5)=3\times 5=15[/tex]
The y-intercept of the function is at (0,15). It means jeremiah's statement is incorrect.
Put f(x)=0, to find the x-intercept.
[tex]0=(x+3)(x+5)[/tex]
[tex]x+3=0\Rightarrow x=-3[/tex]
[tex]x+5=0\Rightarrow x=-5[/tex]
The x-intercepts are at (-3,0) and (-5,0). It means Lindsay's statement is incorrect.
[tex]f(x)=(x+3)(x+5)[/tex]
[tex]f(x)=x^2+8x+15[/tex]
[tex]f(x)=x^2+8x+15+16-16[/tex]
[tex]f(x)=(x^2+8x+16)-1[/tex]
[tex]f(x)=(x+4)^2-1[/tex] .... (1)
The vertex form of a parabola is
[tex]f(x)=(x-h)^2+k[/tex] .... (2)
Where, (h,k) is vertex.
From (1) and (2) it is clear that the vertex of the parabola is (-4,-1), Stephen's claim is correct.
The midpoint between the x-intercepts is
[tex](\frac{-3-5}{2},\frac{0+0}{2})=(-4,0)[/tex]
The midpoint between the x-intercepts is at (-4, 0). It means Alexis's statement is incorrect.
Answer:
On E2020 its Stephen is correct
Step-by-step explanation: